Prevalence and pattern of use of medications amongst undergraduate students of a Nigerian University - Olubunmi Margaret Ogbodu; Ayobami Precious Adekola; Gloria Thupayagale-Tshweneagae (Elsevier, 2023)
University undergraduates in Nigeria use prescription and over-the-counter (OTC) medications for cognitive enhancement and relaxation during examination periods. Such practices can lead to increased toxicity, drug interactions, and other adverse effects. This study investigated the prevalence and pattern of use of prescription and OTC medications amongst undergraduate students at the University of Lagos. Quantitative data were collected from 386 students in 2018. The collected data was analysed using SPSS version 22. The study found that 68% of respondents frequently used prescription and OTC medications, such as non-medical analgesics, caffeine-containing drugs, cough syrups containing codeine, diphenhydramine combinations, bromazepam, antimalarials, and antibiotics, during the examination period. The medications were accessed through community pharmacies and leftover medications at home. The findings highlight the ease of access to these medications as a major contributor to their non-medical use by students. This suggests the need for legislation and a functional regulatory framework to control the sale of medications without a prescription from a qualified medical practitioner and sustained public awareness campaigns on medication use and the potential danger of self-medication.